2004
DOI: 10.1101/lm.76304
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-dependent learning and motor-skill complexity

Abstract: Learning of a procedural motor-skill task is known to progress through a series of unique memory stages. Performance initially improves during training, and continues to improve, without further rehearsal, across subsequent periods of sleep. Here, we investigate how this delayed sleep-dependent learning is affected when the task characteristics are varied across several degrees of difficulty, and whether this improvement differentially enhances individual transitions of the motor-sequence pattern being learned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

39
207
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(255 citation statements)
references
References 43 publications
39
207
4
1
Order By: Relevance
“…We reasoned that, as information would be integrated across the left and right brain hemispheres, consolidation of bimanual learning might be enhanced compared to unimanual. Indeed, after an interval of 24 hours, Kuriyama et al (2004) found enhanced consolidation in bimanual compared to unimanual finger-tapping performance, but this was only when the sequence was complex. A number of fMRI studies have shown that bimanual and unimanual tasks recruit somewhat different neural systems in the early stages of motor training, but it is not yet clear if this has any lasting effect on memory consolidation in sequence-specific learning (Bapi, Doya, & Harner, 2000;Gerloff & Andres, 2002;Sun, Miller, Rao, & D'Esposito, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…We reasoned that, as information would be integrated across the left and right brain hemispheres, consolidation of bimanual learning might be enhanced compared to unimanual. Indeed, after an interval of 24 hours, Kuriyama et al (2004) found enhanced consolidation in bimanual compared to unimanual finger-tapping performance, but this was only when the sequence was complex. A number of fMRI studies have shown that bimanual and unimanual tasks recruit somewhat different neural systems in the early stages of motor training, but it is not yet clear if this has any lasting effect on memory consolidation in sequence-specific learning (Bapi, Doya, & Harner, 2000;Gerloff & Andres, 2002;Sun, Miller, Rao, & D'Esposito, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…wakefulness and time of day (Brawn, Fenn, Nusbaum, & Margoliash, 2010;Cajochen et al, 2004;Della-Maggiore, 2005;Doyon et al, 2009;Fischer, Hallschmid, Elsner, & Born, 2002;Keisler, Ashe, & Willingham, 2007;Kuriyama, Stickgold, & Walker, 2004;Manoach et al, 2004;Maquet, Schwartz, Passingham, & Frith, 2003 The purpose of the present study was to investigate the separate contributions of general motor skill learning and sequence-specific memory consolidation in implicit sequence learning. General motor skill learning refers to faster responses as a result of practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Demonstrations of overnight, sleep-dependent learning have now been reported across both sensory (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000a,b;Fenn et al, 2003;Atienza et al, 2004;Gaab et al, 2004) and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003aKorman et al, 2003;Huber et al, 2004;Robertson et al, 2004;Kuriyama et al, 2004) skill memory domains.…”
mentioning
confidence: 99%